Acute hepatitis E superinfection leading to chronic hepatitis B reactivation. (10th June 2018) - Aslam, Aysha; Susheela, Ammu; Iriana, Sentia; Chan, Suzanne S; Lau, Daryl
Abstract : Reactivation of chronic hepatitis B (CHB) can be associated with significant morbidity and mortality. There are many different causes of hepatitis B reactivation. This case describes an Asian woman with stable CHB presenting with significant hepatitis flare with markedly elevated serum aminotransferases and hepatitis B virus DNA level. The clinical symptoms were subtle with fatigue and vague right upper quadrant tenderness. We ruled out drug-associated hepatotoxicity and screened for common causes of acute hepatitis. Interestingly, she was noted to have reactive anti-hepatitis E virus (HEV) IgM at initial presentation followed by anti-HEV IgG positivity a month later. The serological pattern confirmed the diagnosis of acute hepatitis E. The combination of antiviral therapy for hepatitis B and resolution of acute hepatitis E resulted in normalisation of serum aminotransferases. This case illustrates the importance of taking a careful history and having a high index of suspicion for various aetiologies when evaluating patients with reactivation of CHB.